Tergerusnya kearifan lokal orang Mapur di tengah ekspansi Perkebunan Kelapa Sawit PT. GPL di Dusun Air Abik, Kabupaten Bangka - Darmawan, Budi; Saputra, Putra Pratama; Hidayat, Novendra (Academy of Education Journal, 2024)
This research was conducted with the aim of explaining the erosion of local wisdom among the Mapur people in the utilization of forests amidst the expansion of oil palm plantations by PT. GPL in the Air Abik Hamlet, Bangka Regency. The research used a qualitative descriptive approach. The data collection process was carried out through interviews, observations, documentation, and various secondary data sources, including official documents, mass media reports, scientific articles, books, papers, and previous research reports discussing the Mapur community. The results of this research indicate that since the era of regional autonomy, the local wisdom possessed by the Mapur people has been disrupted due to the presence of oil palm plantation companies, predominantly PT. GPL, expanding land, especially in the Mapur people's customary forests. This expansion, whether realized or not, has taken over most of the customary forest land that has been guarded and preserved for their livelihoods. In addition, the knowledge held by this community about environmental conservation, including the use of natural medicines, codes of conduct, traditional rituals (beume), nujuh jerami, as well as local wisdom about forest utilization, is also gradually eroded along with their existence. The loss of these traditions and local wisdom also means the loss of the identity of the Mapur people, who are the oldest Malay tribe on Bangka Island, living in harmony and wisdom with nature.